Predictors of the Prevalence of Dyslipidemia and Influencing Factors for Young Health Examination Cohort: A Cross-Sectional Survey - Zhang, Hui; Kwapong, William Robert; Shao, Meng-Meng; Yan, Jue-Yue; Lin, Xian-Da; Chen, Bo-Bei; Chen, Ke-Yang (Frontiers in Public Health, 2020)
Objectives: The objective of this study was to estimate the prevalence of dyslipidemia and associated influencing factors in young adults in the southeastern coastal area of China. Methods: This study adopted a cross-sectional survey and included 7,859 young people who underwent examinations at three hospitals in Wenzhou, Zhejiang Province, China. All subjects completed a questionnaire in the form of face-to-face interviews and underwent anthropometric measurements and biochemical tests. The continuous data are presented as the means ± standard deviations and were compared using Student's t-tests. The categorical variables are presented as proportions. The influencing factors associated with dyslipidemia were evaluated through a multivariate logistic regression. Results: The prevalence of dyslipidemia among young adults aged 18–45 years in the southeastern coast of China was high with 7.1, 15.0, 22.9, and 4.0% for high-total cholesterol (TC), high-triglyceride (TG), low-high-density lipoprotein cholesterol (HDL-C), and high-low-density lipoprotein cholesterol (LDL-C). Among those with dyslipidemia, a statistically significant difference in sex was observed, and all types of dyslipidemia were associated with smoking and alcohol consumption. However, those with high-TG, high-LDL, and low-HDL levels did not significantly differ in education level or occupation. The presence of dyslipidemia was significantly associated with increased age, the male sex (OR: 1.85, 95% CI: 1.39–2.21), smoking (OR: 2.02, 95% CI: 1.98–2.13), alcohol consumption (OR: 1.33, 95% CI: 1.16–1.63), overweight or obesity (OR: 2.01, 95% CI: 1.79–2.41), and intellectual work (OR: 1.36, 95% CI: 1.11–1.72). Conclusion: The prevalence of dyslipidemia among young adults aged 18–45 years in the southeastern coast of China was high. To prevent dyslipidemia at an early age, it is essential to conduct effective intervention programs targeting risk factors and to implement routine screening programs.